Remediation of Manufactured Methamphetamine in Clandestine Laboratories. A Literature Review - Owens, Clyde V; Mason, Mark M; Marr, David (ACS Chemical Health & Safety., 2017)
The purpose of the current literature review was to identify, collect, review, and organize all available information concerning clandestine laboratories used to produce methamphetamine through an analysis of routinely collected data sources. There were numerous peer reviewed journals, electronic databases, websites, and commercial vendors relevant to the remediation process of methamphetamine laboratories. Our intention in this review was to produce background information as well as a reference guide relating to the critical problem of methamphetamine production nationally and internationally in addition to generating future research projects associated with the topic. This literature review determined there has not been a national standardized analytical method recognized as a reference guideline for the remediation of clandestine laboratories for production of methamphetamine.